IMPLEMENTASI INTERNET OF THINGS PADA ALAT PEMANTAU ASAP DAN SUHU BERBASIS ARDUINO DI BANDAR UDARA AJI PANGERAN TUMENGGUNG PRANOTO SAMARINDA - Fiqqih Faizah (Approach : Jurnal Teknologi Penerbangan, 2021)
Unit Pelaksana Bandar Udara (UPBU) Class I APT Pranoto Samarinda has a high load of electricity resource usage which results in rotating blackouts because the generator is not able to meet the needs of electricity users who are getting bigger at certain hours. Therefore it is necessary to have a backup power supply from a generator. To keep the generator working properly, it requires maintenance such as checking battery level, diesel fuel supply, engine lubricating oil level, cooling water level, checking voltage, current, and temperature. In addition to maintenance, generator safety must also be considered in order to function properly. Not only the terminal that must be equipped with security, the generator room also needs to be provided with a protection system, for example from fire hazards and toxic gases as side effects. To help monitor the condition of the room, a smoke and temperature monitor was made that utilizes internet of things (IoT) technology by relying on the NodeMCU ESP8266 as the controller. The MQ2 sensor is used to detect smoke or toxic gases as a result of fire hazards or other hazardous gases. Temperature detection using the DHT11 sensor. Notifications in case of disturbances are conveyed to field technicians using a manual system with a buzzer as a sound generator and digital notifications on Android-based phones. Thus, if the technician is away from the location, the technician will still receive information about the condition of the generator room by using his cell phone by using the Blynk application.